Развитие производства твердых сплавов в НТАК «АЛКОН» НАН Украины - Бондаренко, В.П.; Барановский, А.М. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
The brief review of scientific achievements of scientists Bacul Institute for superhard materials National Academy of Sciences of Ukraine confirms that in the field of a science about hardfacing alloys they are among the advanced countries of the world. Their works differ a high level of
originality and are used in the Russian Federation, Uzbekistan, China, a series of other countries,
and effects of explorations are confirmed with a series of advanced firms of Sweden, Czechia, Bulgaria, Poland.